Ion–molecule reactions of CoAr₆⁺ with nitrogen oxides N₂O, NO, and NO₂: measuring absolute pressure by shock-freezing of the collision complex - Linde, C. van der; Höckendorf, R.F.; Balaj, O.P.; Beyer, M.K. (Физика низких температур, 2010)
A new method to determine the absolute pressure in an ultra-high vacuum apparatus is tested using ion molecule reactions with CoAr₆⁺. In a collision with a neutral reactant, the complex between Co⁺ and the collision partner is stabilized by evaporation of argon atoms. If CoAr₆⁺ reacts with collision rate, the absolute pressure can be determined by comparing the experimental collision rate with the collision rate calculated from average dipole orientation theory. The experimental results with N₂O, NO, and NO₂ indeed show that the collision complex is frozen out. Comparison of the rates of primary, secondary and tertiary reaction products, however, suggests that not all collisions of CoAr₆⁺ are reactive.